Pengaruh Pemberian Reward dan Punishment Terhadap Motivasi Belajar Peserta Didik Kelas X Pada Mata Pelajaran Ekonomi di SMAN 1 Sawan, Kabupaten Buleleng - Aryani, Komang Wija Putri; Suwena, Kadek Rai (Jurnal Pendidikan Ekonomi Undiksha, 2023)
The purpose of this research is to find out: (1) the effect of reward on students' learning motivation; (2) the effect of punishment on learning motivation; and (3) the effect of reward and punishment on the motivation of class X learners in economics subjects at SMAN 1 Sawan. This research is causal research with a quantitative method. The population in this study is all Xclass learners at SMAN 1 Sawan. The sample used is 154 students. The sampling technique used is proportional random sampling. The data was collected using a questionnaire and analyzed with descriptive analysis and multiple linear regression analysis. The results showed that descriptive analysis of reward, punishment, and motivation learning is quite good because it is in the range of 71.01-100% in the Three Box Method Criteria. Meanwhile, in the analysis of the t-test and f-tests, namely the provision of rewards and punishments, partially affects the student's learning motivation. While simultaneously giving reward and punishment affects learning motivation.